Tinjauan Hukum Ekonomi Syariah Terhadap Pembiayaan Qarḍ Dengan Akad Mudārabah Di BMT NU Kalitidu Kabupaten Bojonegoro: The Sharia Economic Law Review Of The Practice Of Qarḍ Financing With A Mudārabah Contract At BMT NU Kalitidu Bojonegoro Regency - Hasbi Ash Shiddiqi; Siti Muslimah (ISTIDLAL, 2022)
There are several customers who apply for financing at BMT NU Kalitidu for reasons of meeting their consumptive needs and paying debts, actually the contract that must be used is a qarḍ contract, but because there is no qarḍ product at BMT NU Kalitidu, a mudārabah contract was chosen, which facilitates the collaboration process because they are accustomed to using Mudārabah financing in entering into an agreement. Two things that become problems are first, How is the practice of qarḍ financing with a mudārabah contract at BMT NU Kalitidu, and How is the Sharia Economic Law Review of the practice of qarḍ financing with a mudārabah contract at BMT NU Kalitidu. This research is a field research with the place of research at BMT NU Kalitidu. The data sources include primary data, namely observations and interviews, while secondary data is obtained from reference data sources such as books, journals, articles and others. The method of collecting data in this research is from observation, interviews, and documentation, while the method used to analyze the data is a qualitative. The results of the study are: First, qarḍ financing does not exist in BMT NU Kalitidu, then the need for funds for a consumptive item in BMT NU Kalitidu is the same as mudārabah financing. The provision of funds for consumptive needs with a mudārabah contract is inappropriate (not allowed) because the use of a mudārabah contract must be accompanied by work carried out by the customer with funds from BMT NU Kalitidu.